2001
DOI: 10.1083/jcb.200106089
|View full text |Cite
|
Sign up to set email alerts
|

The actin-binding protein Hip1R associates with clathrin during early stages of endocytosis and promotes clathrin assembly in vitro

Abstract: Huntingtin-interacting protein 1 related (Hip1R) is a novel component of clathrin-coated pits and vesicles and is a mammalian homologue of Sla2p, an actin-binding protein important for both actin organization and endocytosis in yeast. Here, we demonstrate that Hip1R binds via its putative central coiled-coil domain to clathrin, and provide evidence that Hip1R and clathrin are associated in vivo at sites of endocytosis. First, real-time analysis of Hip1R–YFP and DsRed–clathrin light chain (LC) in live cells rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
226
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 242 publications
(243 citation statements)
references
References 46 publications
16
226
1
Order By: Relevance
“…It is generally accepted that actin polymerization plays a role in some (but not all, see [52,53]) forms of CME [9,11,18,44,46,47,50,54]. Here, a more accurate measurement of actin dynamics using the ppH assay revealed an ordered sequence of proteins involved in actin dynamics.…”
Section: Sequential Recruitment Of Positive and Negative Regulators Omentioning
confidence: 81%
See 1 more Smart Citation
“…It is generally accepted that actin polymerization plays a role in some (but not all, see [52,53]) forms of CME [9,11,18,44,46,47,50,54]. Here, a more accurate measurement of actin dynamics using the ppH assay revealed an ordered sequence of proteins involved in actin dynamics.…”
Section: Sequential Recruitment Of Positive and Negative Regulators Omentioning
confidence: 81%
“…Other proteins showed a similar pattern of biphasic recruitment and thus defined a dynamin module. These included actin-binding proteins such as the actin-and clathrin-binding protein Hip1R [44] as well as the motor protein myosin6, which binds actin and the adaptor protein Dab2 [45]. Other proteins involved in actin dynamics and grouped in the dynamin module included the Arp2/ 3 activator N-WASP [46,47], Eps8, an actin capping protein that forms a complex with Abi1 and binds N-WASP [33] and the motor protein myosin1E [48].…”
Section: The Dynamin/myosin Modulementioning
confidence: 99%
“…These sorts of intimate and persistent actin/clathrin associations were not seen in control HeLa cells grown without exposure to the "A3" siRNA (unpublished data), nor have they been seen before in any of a wide variety of other cultured cells examined by unroofing over the years (Heuser, 1980;Heuser and Anderson, 1989;Fujimoto et al, 2000;Engqvist-Goldstein et al, 2001). In addition, the collections of F-actin filaments observed in A3 cells have an unusual configuration, not commonly observed on the ventral surfaces of these HeLa (or any other) cultured cells.…”
Section: The Cortical F-actin Structures Appear To Be Tethered To Thementioning
confidence: 82%
“…We found that cortactin, the Arp2/3 complex and Abp1 are enriched in these structures (Figure 3 and unpublished data). Similar to Hip1R, cortactin, and Abp1 are actin-binding proteins implicated in both endocytic and actin functions, and they may function at the interface between the actin cytoskeleton and the endocytic machinery (Kessels et al, 2000(Kessels et al, , 2001McNiven et al, 2000;Cao et al, 2003;Mise-Omata et al, 2003). Cortactin and Abp1 both colocalize with the Arp2/3 complex in cells (Kessels et al, 2000;McNiven et al, 2000).…”
Section: Accumulation Of Cortical Actin Tails and Other Unusual Cortimentioning
confidence: 99%
See 1 more Smart Citation